Assessment of qualitaty of quasigeoid models in Riga city - Celms, A.; Trevoho, I.; Kolodiy, P.; Pukite, V.; Virkavs, M.; Lidumnieks, T. (Видавництво Львівської політехніки, 2023)
The study of the shape and size of the globe on a global scale is crucial to understanding the challenges and impacts of climate, the life sciences, hydrology, hydrography and geology on the planet as a whole. The Earth's topography – the surface, the relief topography that characterizes two different types of regions and certain local urban areas - is varied and changes occur periodically. The practical significance is to create a homogeneous geodetic reference system and geodetic frame based on certainty and reliability. A dynamic model of the globe could solve many future problems. Determining the topographic surface of the Earth - the altitude above sea level – using precise levelling methods is laborious task. Today, satellite-based measurement methods - GNSS - are used. GNSS allows to determine ellipsoidal heights using satellite systems and the global ellipsoidal model parameters (X,Y,Z). The geoid – surface of the mean sea level will enable to derive normal height from ellipsoidal heights; Then compared with the normal heights of the geometric levelling method. The need for a geoid or quasigeoid model in the economy is important for construction, navigation, logistics, users and maintainers of geographic information systems. A high-precision geoid or quasigeoid model would make a qualitative contribution to real-time GNSS measurements. The theoretical part of the study gives an overview of the shape and modelling of the globe; technological methods for the development of geoid and quasigeoid models; characteristics of geoid and quasigeoid models. The study includes GNSS measurements on known Class 1 leveling line points - obtaining ellipsoidal height values at 8 selected points in the southern part of Riga city. The obtained measurements were processed and the data were compared with available geoid and quasi-geoid models.
Keywords: geoid; quasigeoid; height systems; GNSS/levelling; 528.45(474.362.2)